PENGARUH VARIASI PRODUK KUE DAN KUALITAS PELAYANAN TERHADAP MINAT BELI PADA TOKO TATA BAKERY CABANG LINGKAR BARAT KOTA BENGKULU - Apita Cesilia; Sri Ekowati (UM. Bengkulu, 2022)
This study aimed to find out the effect of cake product variations and service quality on buying interest at the Tata Bakery Shop,Lingkar Barat Branch,Bengkulu City.This Study applied the type of quantiative descriptive research.The object of this study was the consumer at Tata Bakery wich is located on the lingkar barat,bengkulu city.the sampling method employed a non-probability technique,namely accidental sampling.The number ofrespondents in this study were 130 people.This study used a collection method in the form of a questionnaire.To analyze the data,this research uses multiple linear regression analysis test,and hypothesis testing,namely t-test and f-test.the results of the study conclude that the variabel cake product variations had a positive effect on buying interest,service quality contributed to a positive effect on buying interest,and cake product variations,and service quality together had a positive and significant effect on buying interest. Keywords: Cake Product Variation, Service Quality,Buying Interest